Integrating the circular economy model into the management and treatment of Fischer–Tropsch effluents—a conversion of waste to energy (biogas) opportunity - Mabatho Moreroa; Thapelo P. Malematja; Grace Nkechinyere Ijoma (IET Renewable Power Generation)
Abstract The Fischer–Tropsch (FT) process converts coal, biomass, or natural gas into liquid hydrocarbons via syngas generation and catalytic conversion. However, FT produces byproducts and effluents with substantial environmental consequences. This review explores the circular economy model's potential as a sustainable wastewater management strategy for FT effluent management. Furthermore, the paper investigates ameliorative measures to overcome the limitations of one biological treatment method, anaerobic digestion of FT effluents by examining the combination of nutrient augmentation, microbial augmentation, and enrichment from the integration of wastes derived from other industrial sectors as pivotal to the implementation of circular economics modelling in FT effluents valuation. This approach to the circular economy model can help overcome the environmental concerns posed by FT effluents in its advocacy of resource sharing, reuse, and recycling. This review also promotes circular economy principles to improve resource recovery, recycling, and collaboration with other industrial sectors, such as agriculture and mining, with FT application industries to create a more sustainable economy and reduce their environmental footprints. However, since the chemical compositions of wastes vary with location and other parameters, future case studies should optimize the waste mixtures to determine the optimal balance before valorizing them.